Different criteria for feed formulation based on digestible amino acids for broilers - Araújo, L. F. (2006)
An experiment was carried out to evaluate different criteria in feed formulation based on digestible amino acids for broilers during the grower phase. Diets were formulated according to the recommendations for digestible methionine, methionine + cysteine, lysine, and threonine. A total number of six hundred Cobb 500 male day-old chicks were distributed in a completely randomized experimental design, with three formulation criteria supplying the recommendations established by Baker & Chung (1992), Degussa (1997), and Rostagno et al. (2000), with 4 replicates of 50 birds each. No significant differences were observed for weight gain and feed intake. However, feed conversion ratio improved when birds were fed the diets containing the profiles recommended by Baker & Chung (1992) and Degussa (1997). No difference was observed in terms of leg, wings, back, and head yields. Broilers fed with the profile of Baker & Chung (1992) presented worst breast yield, whereas those fed the Degussa (1997) standard had better carcass yield.